2021
DOI: 10.3389/fimmu.2021.685214
|View full text |Cite
|
Sign up to set email alerts
|

The N-Formyl Peptide Receptors and Rheumatoid Arthritis: A Dangerous Liaison or Confusing Relationship?

Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by a progressive symmetric inflammation of the joints resulting in bone erosion and cartilage destruction with a progressive loss of function and joint deformity. An increased number of findings support the role of innate immunity in RA: many innate immune mechanisms are responsible for producing several cytokines and chemokines involved in RA pathogenesis, such as Tumor Necrosis Factor (TNF)-α, interleukin (IL)-6, and IL-1. Pattern recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…RA is a chronic autoimmune disease characterized by a progressive symmetric inflammation of the joints resulting in bone erosion, cartilage destruction, progressive loss of function, and joint deformity [ 111 ], mediated by both adaptative [ 112 ] and innate immunity [ 113 , 114 , 115 ]. Calcinosis cutis associated with RA is extremely rare, and few cases have been reported to date [ 14 , 16 , 116 ].…”
Section: Calcinosis Cutis and Other Autoimmune Conditionsmentioning
confidence: 99%
“…RA is a chronic autoimmune disease characterized by a progressive symmetric inflammation of the joints resulting in bone erosion, cartilage destruction, progressive loss of function, and joint deformity [ 111 ], mediated by both adaptative [ 112 ] and innate immunity [ 113 , 114 , 115 ]. Calcinosis cutis associated with RA is extremely rare, and few cases have been reported to date [ 14 , 16 , 116 ].…”
Section: Calcinosis Cutis and Other Autoimmune Conditionsmentioning
confidence: 99%
“…As a preliminary step, we analyzed the effects of Nitrodi’s water by Western blot on the activation of extracellular signal-regulated protein kinases 1 and 2 (ERK 1/2), which are members of the mitogen-activated protein kinase super-family that regulates growth and cell-cycle progression. Serum-starved BJ cells were treated with PBS alone (as a negative control), Nitrodi, or fMLF (as a positive control) for ERK 1/2 activation [ 31 , 32 , 33 ]. Figure 1 A shows that the incubation with Nitrodi for 5 min significantly increased the phosphorylation of ERK 2, but not of ERK 1, thus suggesting that Nitrodi’s water could act on BJ cell proliferation and cell-cycle progression.…”
Section: Resultsmentioning
confidence: 99%
“…Wang ( Wang et al, 2020 ) et al showed that miR-483-3p promoted cell proliferation of FLS in RA by targeting IGF-1. It has been reported that many innate immune mechanisms produce cytokines and chemokines, such as tumor necrosis factor TNF-α, IL-6, and IL-1, involved in the pathogenesis of RA ( Mormile et al, 2021 ). In addition, clinical studies have shown that CD14-positive monocytes from RA patients are more resistant to apoptosis, thereby promoting their persistence at the site of inflammation ( Ren et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%